The early history of the Book and Archival Heritage Institute Library of the Tuscany Region, Italy (SBL): (1972-1984) - Mauro Guerrini (JLIS.it, 2021)
The essay presents the history of the library of the Service for Book and Archival Heritage of the Region of Tuscany (SBL) from 1972, the year of its foundation, to 1984, the year of Luigi Crocetti’s retirement. The contribution moves on the double track of historical research and the personal memories of some protagonists. The library is characterized by being a unique case in Italy: a reference point for Tuscan and Italian librarians.